To divide the polynomial \( 4x^4 + 4x - 10 \) by \( 2x^2 - 3 \), we can use polynomial long division.
-
Divide the leading term of the dividend \( 4x^4 \) by the leading term of the divisor \( 2x^2 \): \[ \frac{4x^4}{2x^2} = 2x^2 \]
-
Multiply the entire divisor \( 2x^2 - 3 \) by \( 2x^2 \): \[ 2x^2(2x^2 - 3) = 4x^4 - 6x^2 \]
-
Subtract this from the original polynomial: \[ (4x^4 + 4x - 10) - (4x^4 - 6x^2) = 4x + 6x^2 - 10 = 6x^2 + 4x - 10 \]
-
Now divide the leading term \( 6x^2 \) by the leading term of the divisor \( 2x^2 \): \[ \frac{6x^2}{2x^2} = 3 \]
-
Multiply the entire divisor \( 2x^2 - 3 \) by \( 3 \): \[ 3(2x^2 - 3) = 6x^2 - 9 \]
-
Subtract this from the current remainder: \[ (6x^2 + 4x - 10) - (6x^2 - 9) = 4x - 10 + 9 = 4x - 1 \]
Now we have completed the division. The quotient is \( 2x^2 + 3 \), and the remainder is \( 4x - 1 \).
Thus, the correct response is:
The quotient is \( 2x^2 + 3 \). The remainder is \( 4x - 1 \).